Speech and computer : 17th International Conference, SPECOM 2015, Athens, Greece, September 20-24, 2015, Proceedings /: 17th International Conference, SPECOM 2015, Athens, Greece, September 20-24, 2015, Proceedings. (2015) - Unknown
No abstract available